Highly conductive carbon nanotube micro-spherical network for high-rate silicon anode - Park, Byung Hoon; Jeong, Jun Hui; Lee, Geon-Woo; Kim, Young-Hwan; Roh, Kwang Chul; Kim, Kwang-Bum (Journal of power sources, 2018)
We report on a highly conductive CNT micro-spherical network for high-rate silicon anode materials prepared by one-pot spray drying for lithium-ion batteries. The anode material contains silicon nanoparticles bound to CNTs through a small amount of sucrose-derived carbon. The first charge and discharge capacities of the Si/CNT/C microsphere electrode are measured to be 3152 and 2302 mA h g−1 of the composite, respectively, at 0.1 A g−1. The Si/CNT/C microsphere electrode exhibits an initial capacity of 1989 mA h g−1 at current density of 1.0 A g−1 and retains ∼70% of the initial capacity after 100 cycles. Even at a high current density of 10 A g−1, the Si/CNT/C microsphere electrode exhibits a capacity of 784 mA h g−1 with a stable charge/discharge behavior. The superior rate capability of the Si/CNT/C microsphere composites can be attributable to the unhindered Li-ion transport through the highly conductive CNT buffer matrix, to which Si NPs are strongly bound by the sucrose-derived carbon. These salient results give further impetus to the study of CNTs for use as a buffer matrix to improve the rate capability of high-capacity electrode materials with large volume changes during charge storage. •Si NPs are bound to CNT network through a very tiny amount of sucrose-derived carbon.•The Si/CNT/C microsphere has an interconnected pore facilitating Li-ion transport.•The Si/CNT/C microsphere exhibited superior rate capability with high capacity.